Teachers’ Attitudes towards Using Cooperative Learning through Technology for Developing Writing Skills in a Military Context - Chkotua, Maia; Kharchilava, Maia (European Scientific Journal, ESJ, 2025)
Teachers of English for Specific Purposes (ESP) consider writing one of the most challenging productive skills for military students to master. Writing is a vital skill for their future careers, as they must pass the high-stakes STANAG 6001 (Standardisation Agreement 6001) test for promotion. Teachers play a crucial role in teaching ESP by addressing students’ current needs and designing goal-oriented assignments to develop their writing skills and improve performance. Therefore, the purpose of the study was to explore ESP teachers’ attitudes toward using cooperative learning through technology to enhance writing skills and to assess their readiness to implement this instructional strategy, since successful implementation largely depends on teachers’ attitudes. The study used a quantitative approach. Data were collected through a questionnaire and analyzed with descriptive statistics. Participants included 58 teachers from various military educational institutions in NATO member, partner, and candidate countries such as Georgia, Ukraine, Latvia, and the UK. SPSS 27 was used for data analysis. The results show that most ESP teachers have positive attitudes toward using cooperative learning via technology to develop writing skills, as it can foster cooperation among English language learners. Although teachers note that students lack the necessary skills for effective cooperative group work and that the method places too much responsibility on students, these findings suggest that this complex approach has the potential to help military students improve their writing performance.